2008
DOI: 10.1186/1471-2393-8-42
|View full text |Cite
|
Sign up to set email alerts
|

The difficulties of conducting maternal death reviews in Malawi

Abstract: Background: Maternal death reviews is a tool widely recommended to improve the quality of obstetric care and reduce maternal mortality. Our aim was to explore the challenges encountered in the process of facility-based maternal death review in Malawi, and to suggest sustainable and logically sound solutions to these challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 9 publications
3
88
0
2
Order By: Relevance
“…In places where establishment of maternal mortality audits has led to improved quality of obstetric care, the success has been particularly attributed to strong leadership and accountability of both health providers and key decision makers [7,11,25,26]. Our findings recommend a more responsive health system from the level of the ministry of health down to the grass root levels.…”
Section: Discussionmentioning
confidence: 82%
“…In places where establishment of maternal mortality audits has led to improved quality of obstetric care, the success has been particularly attributed to strong leadership and accountability of both health providers and key decision makers [7,11,25,26]. Our findings recommend a more responsive health system from the level of the ministry of health down to the grass root levels.…”
Section: Discussionmentioning
confidence: 82%
“…There are challenges to conducting an MDA [25,26]. These include fear of repercussions, lack of anonymity during audit sessions, resistance of healthcare providers to have their care evaluated by peers or to evaluate care given by peers, lack of staff commitment, and lack of knowledge and skills among some healthcare providers.…”
Section: Auditmentioning
confidence: 99%
“…Standards should be set with a clear objective, and structure, process, and outcome criteria need to be clearly defined. The standards and criteria for audit can be developed by expert teams or by the QI teams themselves [26]. The latter enhances ownership of the QI process by those implementing the changes at service-delivery level.…”
Section: Auditmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is worrying that the rate of implementation of recommendations made by audit committees was 30% in the present study. However, it has been suggested that healthcare managers and staff-owing to health system weaknesses-face difficulties in using the audit process and its recommendations to improve quality of care [8]. This calls for institutionalization of the implementation of audit committee recommendations and the setting up of systems to monitor progress toward reducing maternal deaths.…”
Section: Discussionmentioning
confidence: 96%